Vitamin D supplementation and body weight status: a systematic review and meta-analysis of randomized controlled trials - Pathak, K.; Soares, Mario; Calton, Emily; Zhao, Yun; Hallett, Jonathan (Wiley-Blackwell Publishing Ltd., 2014)
Vitamin D is anticipated to have many extra-skeletal health benefits. We questioned whether supplementation with the vitamin influenced body weight and composition. A systematic review and meta-analysis was conducted on high-quality, randomized controlled trials (RCTs) that had supplemented vitamin D without imposing any caloric restriction. Eighteen trials reporting either body weight, body mass index (BMI), fat mass (FM), percentage fat mass (%FM) or lean body mass (LBM) met our criteria. Twelve studies provided the required data for the meta-analysis. Vitamin D supplementation did not influence the standardized mean difference (SMD) for body weight, FM, %FM or LBM. A small but non-significant decrease in BMI (SMD = -0.097, 95% confidence interval: [-0.210, 0.016], P = 0.092) was observed. Meta-regression confirmed that neither the absolute vitamin D status achieved nor its change from baseline influenced the SMD of any obesity measure. However, increasing age of the subjects predicted a shift in the SMD for FM towards the placebo treatment, whereas a greater percentage of women in these studies favoured a decrease in FM following vitamin D. Vitamin D supplementation did not decrease measures of adiposity in the absence of caloric restriction. A potential confounding by age and gender was encountered.